Penerapan Metode Pembelajaran Luar Kelas (Outdoor Learning Method) Dalam Meningkatkan Motivasi Belajar Terhadap Pembelajaran IPS di Kelas IV SDN No. 145 Inpres Bayowa Kabupaten Takalar - Nurul Mutakhara; Nursalam Nursalam; Fitri Yanty Muchtar (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to find out whether the Outdoor Learning Method was effectively applied to social studies learning in class IV SDN No. 145 Bayowa Presidential Instruction, Takalar Regency. This type of research is quasi-experimental research. The sample in this study were 19 students. Data collection techniques were carried out using questionnaires, learning achievement tests and observation sheets. The data analysis technique in this study is a descriptive data analysis technique and the T-Test.The results showed that students' learning motivation in social studies learning prior to the implementation of the outdoor learning method was generally in the less motivated category and student learning outcomes were in the pretest with an average score of 45.7. Meanwhile, students' learning motivation in social studies learning after the implementation of the outdoor learning method increased to a motivated category and student learning outcomes in the posttest with an average score of 86.8. It can be concluded that the application of the outdoor learning method is effectively used in thematic learning of fourth grade students at SDN No. 145 Bayowa Presidential Instruction, Takalar Regency. The results of descriptive and inferential analysis testing with the help of SPSS 23.0 for windows. The normality test of the pretest and posttest data was normally distributed with a Sig value of 0.20 > α = 0.05 and the results of the hypothesis test using the One Sample t-test t-test and obtained a p value (sig.(2-tailed)) was 0.000 <0.05, so that H0 is rejected and H1 is accepted, which means that there is an increase in social studies learning outcomes after applying the outdoor learning method to fourth grade students at SDN No. 145 Bayowa Presidential Instruction, Takalar Regency, with a gain value of more than 0.30. Thus the researchers concluded that the outdoor learning method was quite effective in improving social studies learning outcomes for fourth graders of SDN No. 145 Bayowa Presidential Instruction, Takalar Regency.